GROUND SUBSIDENCE CAUSED BY EARTHQUAKE TYPE EXCITATION - H. B. Poorooshasb; A. Noorzad (International Association of Lowland Technology, 1999)
The extended CANAsand constitutive model, which incorporates the newly proposed concept of the